Cycling in older adults: a scoping review - Kardan, Mohammadhossein; Akter, Taiyeba; Iqbal, Mehvish; Tcymbal, Antonina; Messing, Sven; Gelius, Peter; Abu-Omar, Karim (Frontiers in Sports and Active Living, 2023)
Introduction: Regular Physical Activity (PA) provides many health benefits to older adults. As a well-known form of physical activity, bicycling can be an appropriate means for older people to meet WHO PA recommendations and to improve their health. In addition, outdoor bicycling (OB) for transport can help to protect the environment and reduce greenhouse gas emissions. The primary aim of this scoping review is to identify the currently available scientific evidence and gaps of research in this field. Methods: A systematic search in 7 databases resulted in 7192 studies. After the exclusion of duplicates, studies were screened by two independent reviewers in a two-stage process. Based on previously defined inclusion criteria, 123 studies were included. Data extraction was based on a descriptive analytical method, and 7 categories for the main focuses of studies were developed. Data were extracted by 3 reviewers to analyze different characteristics of included articles such as age range, study design, date type, gender, type of bicycle, and country of origin. Results: The included studies covered the following topics: (1) traffic safety, (2) bicycling as PA or transportation, (3) health benefits, (4) environmental factors, (5) facilitators and barriers, (6) application of technology and (7) promotion of bicycling. Results show that the majority of studies were performed in both younger (60-79 years) and older (80+ years) adults. Most studies had an observational study design, used conventional bicycles, and were based on quantitative methods. Researchers from the United States, Netherlands, and Japan published the highest number of studies related to different aspects of OB. Discussion: Traffic safety was the most prevalent focus of the included studies. Gaps were identified with regards to studies focusing on the promotion of bicycling, application of technology, as well as facilitators and barriers of bicycling. While research on traffic safety should continue to be a high priority for public health, potentially more research should focus on how to get older people to bicycle more. This is warranted by the proven individual and planetary health benefits of bicycling and the urgency of combating climate change.